Surveillance for adverse events following immunization with DTaP-containing combination vaccines in Linping, China, 2019–2022 - Chen, Qinghua; Zhang, Chuandi; Ye, Chunmei; Zhu, Junwei; Shen, Jie; Zhu, Chang; Yang, Pai; Liu, Tiane; Xu, Yuyang (Frontiers in Public Health, 2024)
The DTaP-Hib and DTaP-IPV/Hib combination vaccine can be used as a substitute for the diphtheria, tetanus, and acellular pertussis combined vaccine (DTaP). We aimed to evaluate the safety of multi-component vaccines containing DTaP by analysing the reporting rates and characteristics of adverse events following immunization (AEFIs) in Linping District during the years 2019 to 2022. We obtained data of AEFI and vaccination from the National AEFI Surveillance System of China and Zhejiang Municipal Immunization Information Management System, respectively, during 2019 to 2022 for a descriptive, epidemiological analysis. The total number of AEFI reported following vaccinations with DTaP-containing combination vaccines was 802 in Linping District from 2019 to 2022. The overall reporting rates of AEFIs following DTaP, DTaP-Hib, and DTaP-IPV/Hib vaccinations were 445.72 (537 cases), 536.29 (45 cases), and 306.13 (220 cases) per 100,000 doses in Linping District from 2019 to 2022, respectively. Only one case of a serious AEFI following DTaP vaccination, with a reporting rate of 0.83 per 100,000 doses. The composition ratio of vaccine product-related reactions for DTaP, DTaP-Hib, and DTaP-IPV/Hib were 99.81%, 97.78%, and 100.00%, respectively. The composition ratio of coincidental events for DTaP and DTaP-Hib were 0.19% and 2.22%, respectively. The reporting rates of total AEFIs for DTaP-IPV/Hib were lower than for DTaP. The reporting rate of local induration for DTaP-Hib was lower than for DTaP, and the reporting rates of local redness & swelling and local induration for DTaP-IPV/Hib were both lower than for DTaP. DTaP-IPV/Hib had a higher proportion of AEFIs in 1st quarter compared to DTaP. The reporting rate after the second dose of DTaP-Hib was higher than that of DTaP, and the reporting rates of AEFIs after the first dose and third dose of DTaP-IPV/Hib were lower than DTaP. The reported AEFIs to multi-component vaccines containing DTaP components during 2019 to 2022 in Linping District were mainly mild vaccine reactions. DTaP-containing combination vaccines demonstrated a good safety profile.